The Nexus of organizational Culture and Work Performance: The Mediating Role of Organizational Politics in Local Government Setting - Lederle Ortega; Jed P. Acero (Global Review of Tourism and Social Sciences, 2025)
This study explores the relationship between organizational culture, organizational politics, and work performance in local government units (LGUs) in the Philippines, focusing on the mediating role of organizational politics. Data was collected from 263 LGU employees with at least three years of experience. Mediation analysis was conducted using validated instruments to measure organizational culture, politics, and work performance. Statistical methods, including the Sobel-Z test, were applied to examine mediation effects. The results show that organizational politics partially mediates the relationship between organizational culture and work performance. A positive culture significantly enhances employee performance, but internal politics mediate this effect. The Sobel-Z test confirmed the significance of the mediation (z = 3.403, p < 0.05), with organizational politics accounting for 15.1% of the total effect. This study advances organizational behavior research by highlighting the mediating role of politics in LGUs. It offers practical insights, recommending that LGUs promote strong organizational cultures and transparent governance to reduce the adverse effects of internal politics, thereby improving employee performance and public service delivery